Lao People's Democratic Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper and Statistical Appendix for the Lao People's Democratic Republic underlies debt sustainability analysis. Sensitivity analysis reveals that if the pace of economic reforms falters, the debt burden-high even in the baseline case-could become unsustainable. The low level of development and the high share of the subsistence agricultural sector limit the revenue collection capacity. Weak technical capacity and highly fragmented revenue administration are the main structural weaknesses affecting revenue performance.